Children on long-term ventilatory support: 10 years of progress. Issue 11 (24th November 2010) - Wallis, C; Paton, J Y; Beaton, S; Jardine, E
Abstract : Objectives: To identify the number and current location of all children receiving long-term ventilation (LTV) in the UK, and to establish their underlying diagnoses and ventilatory requirements. Design: Single time-point census completed by members of the UK LTV working party using an electronic-based questionnaire Subjects: All children in the UK at home or in hospital who, when medically stable, continue to need a mechanical aid for breathing following a failure to wean beyond a 3-month period. Results: 933 children under the age of 17 years in 30 regional centres were identified as receiving LTV. 88 children (9.5%) required continuous positive pressure ventilation by tracheostomy over 24 h, while 658 received ventilation while asleep only. Most children are ventilated by a non-invasive mask (n=704; 75%) or tracheostomy (n=206; 22%). Underlying conditions included neuromuscular disease (n=402; 43%), chronic respiratory (n=343; 37%) and central nervous system conditions (n=168; 18%). 129 (14%) children were aged 16 or over. 844 (91%) children were cared for at home with only 49 children listed as being in acute hospital units (n=34) or paediatric intensive care units/high dependency units (n=15). Conclusions: The last 10 years has seen a very significant increase in the number of children requiring LTV in the UK with an increasing number cared for at home. This reflects both improving technology and increasing clinical expertise in paediatric non-invasive ventilatory support, and a continuing change in attitude towards long-term support, particularly in children with neuromuscular diseases. There are a substantial number of children who soon will require transition to adult services, yet few such services currently exist.